A assistência à saúde em São Mateus/ES: história e atuação do farmacêutico Roberto Arnizaut Silvares (1930 a 1945) - Silveira, Marília Alves Chaves (2023)
We chose as our object of study the trajectory of the pharmacist and politician Roberto Arnizaut Silvares, in the city of São Mateus-ES. Roberto followed his father's path by becoming a practical pharmacist working in the family establishment until he opened his own that bore his name. We should emphasize that pharmacies also acted as medical offices, serving in cases of first aid, minor surgeries and even amputations, that is, the owners of these establishments accumulated a lot of symbolic capital in front of the population's need. In this aspect, in the light of the concept of symbolic power of the sociologist Pierre Bourdieu (1998), symbolic capital is that built by previous generations, throughout history, and that gains space as strategies dominated by the agents who have control of the field. This symbolic capital gave Roberto enough influence to succeed in the political field. Thus, he was elected State Deputy between 1947 and 1950, mayor of São Mateus for two terms, from 1955 to 1959 and from 1963 to 1967, and councilor between 1959 and 1963. In this range, we still have as references the notes of Sabina Loriga (1998) and Avelar (2010) for mapping trajectories. Given the above, we intend to trace Roberto Silvares' trajectory, as well as assess to what extent his family's pharmaceutical performance influenced the success of his political life. Furthermore, we seek to evaluate our character's welfare measures in the region of São Mateus-ES.